Entrepreneurship and the process of firms' entry, survival and growth - Enrico Santarelli; Marco Vivarelli (Institute for the Study of Labor (IZA), 2006)
This survey paper aims at critically discussing the recent literature on firm formation and survival and the growth of new-born firms. The basic purpose is to single out the microeconomic entrepreneurial foundations of industrial dynamics (entry and exit) and to characterise the founder's ex-ante features in terms of likely ex-post business performance. The main conclusion is that entry of new firms is heterogeneous with innovative entrepreneurs being found together with passive followers, over-optimist gamblers and even escapees from unemployment. Since founders are heterogeneous and may make entry mistakes, policy incentives should be highly selective, favouring nascent entrepreneurs endowed with progressive motivation and promising predictors of better business performance. This would lead to the least distortion in the post-entry market selection of efficient entrepreneurs.
urn:nbn:de:101:1-2008051649
Keywords: 330; Unternehmer; Markteintritt; Unternehmenswachstum; Unternehmensentwicklung